PENGARUH MEKANISME CORPORATE GOVERNANCE, LEVERAGE,DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Syafira, Nurul (Faculty of Economics and Business Universitas Jenderal Soedirman, 2014)
Purpose of this research is to examine influence of Corporate Governance mechanism, leverage, and profitability to firm’s value of manufacturing companies listed at Indonesian Stock Exchange during 2010-2012. Firm’s value is calculated by using Tobin’s Q. Meanwhile Corporate Governance mechanism is measured by board of director, independent commissioners, institutional ownership, and audit committee. Samples used in this research are manufacturing companies listed at Indonesian Stock Exchange on period 2010-2012. This research uses purposive sampling method to choose samples so it is resulted 30 companies as samples. Data is analyzed by using multiple regression method. This study finds that board of director, independent commissioners, leverage and profitability has significant positive effect to firm’s value. Besides, this research proves there is significant negative influence from institutional ownership on firm’s value. Whereas, other variables that is audit committee have no significant effect to firm’s value